A systematic review of cognitive telerehabilitation in patients with cognitive dysfunction - Hyeonwoo Jeon; Doo Young Kim; Si-Woon Park; Bum-Suk Lee; Hyeong-Wook Han; Namo Jeon; Minsong Kim; Mingu Kang; Suebeen Kim (Frontiers in Neurology)
IntroductionOne of the possible treatment options for patient with cognitive dysfunction is cognitive telerehabilitation. Previous systematic reviews on cognitive telerehabilitation have focused on specific disease groups and the analysis of intervention methods did not differentiate between traditional face-to-face cognition treatment and usual care. In this systematic review, we aim to analyze randomized controlled trials (RCTs) that compare telerehabilitation with face-to-face treatment or usual care for improving cognitive function in elderly individuals with cognitive dysfunction or patients with acquired brain injury.MethodsWe conducted this systematic review following the guidelines of the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). In this systematic review, we searched 7 electronic databases (PubMed, Cochrane, EMbase, CINAHL, Web of Science, Scopus, KMbase) to identify relevant studies published through December 10, 2024. We conducted a meta-analysis to assess the quality of the studies and synthesize the evidence. Certainty of evidence was evaluated using the Grading of Recommendations, Assessment, Development, and Evaluation (GRADE) method.ResultsFinally, 16 studies were included in the analysis. For comparing telerehabilitation with face-to-face cognition treatment, the meta-analysis included 2 RCTs for global cognition (immediate outcome), 2 RCTs for attention (immediate outcome), 2 RCTs for visuospatial function (immediate outcome). For comparing telerehabilitation with usual care, the meta-analysis included 7 RCTs for global cognition (immediate outcome), 3 RCTs for global cognition (persistence outcome), 4 RCTs for attention (immediate outcome), 3 RCTs for executive function (immediate outcome), 3 RCTs for working memory (immediate outcome), 3 RCTs for visuospatial function (immediate outcome).DiscussionTelerehabilitation has been shown to be more effective than usual care in improving global cognitive function, and its effectiveness is not inferior to that of traditional face-to-face cognitive treatment. By overcoming the limitations of traditional cognition rehabilitation and providing continuous treatment, telerehabilitation can offer effective treatment in specific situations.